PRE-SERVICE TEACHERS’ READINESS ON THE USE OF MOBILE-ASSISTED LANGUAGE LEARNING DURING ONLINE CLASSES - Benita Rachmawati; Fauzi Miftakh; Wahyudin Fitriyana (Journal of English Language and Education, 2021)
This study discussed how the readiness of pre-service EFL teachers to use MALL in their teaching practice activities. In investigating pre-service teachers' readiness, there are two research questions related to the attitudes shown by pre-service teachers towards MALL and their experiences with MALL during their teaching practice. In this study, two types of data collection were used: interviews as the primary data collection and supported by questionnaire. There were four participants involved in this study using the phenomenological study method. This study found that pre-service EFL teachers showed a positive attitude towards the use of MALL. The participants felt that using MALL in their teaching practicum, especially during the Covid-19 pandemic, was very useful. In addition, they also had quite a good experience during their teaching practice using MALL. They can choose the media or platform used according to their learning needs and their respective classroom situations. With the findings obtained, this can be a hope for their future class. The participants are aware of the benefits of MALL and are willing to use it during their teaching practice.